2021
DOI: 10.1101/2021.01.21.427664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximity and Touch are associated with Neural but not Physiological Synchrony in Naturalistic Mother-Infant Interactions

Abstract: Caregiver touch plays a vital role in infants’ growth and development across mammalian species, yet its potential role as a communicative signal in human parent-infant interactions has been sparsely investigated this far. We assessed whether touch enhances neural and physiological synchrony in caregiver-infant dyads. We simultaneously measured brain activity (through functional near-infrared spectroscopy) and respiratory sinus arrhythmia (through electrocardiography) of 69 4- to 6-month-old infants and their m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
1
3
0
Order By: Relevance
“…In addition, we did not find an association between infants' previous synchrony experiences and their displays of positive affect and vocalisations during miscoordination. This null finding is consistent with existing evidence showing that interpersonal synchrony guides infants' regulatory attempts to reinstate homeostasis during bouts of negative affect (e.g., Nguyen et al, 2021;Wass et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we did not find an association between infants' previous synchrony experiences and their displays of positive affect and vocalisations during miscoordination. This null finding is consistent with existing evidence showing that interpersonal synchrony guides infants' regulatory attempts to reinstate homeostasis during bouts of negative affect (e.g., Nguyen et al, 2021;Wass et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Our choice of physiology data to collect, the tool (Empatica E4 wristband) and the continuous variables averaging arousal across phases that were subjected to analyses may not have been the most sensitive to detect any differences across phases or conditions. This is supported by vast methodological differences and unique considerations pertaining to measures of arousal, such as differential effects in tonic but not phasic measures, lack of relationship between heart rate and skin conductance measures, and between physiological measures and neural or behavioral measures of synchrony (Wass et al, 2015;Mønster et al, 2016;Kragness and Cirelli, 2021;Nguyen et al, 2021). There is also evidence for individual differences in arousal levels and complexities associated with its measurement (e.g., Pijeira-Díaz et al, 2019), contributing to our lack of confidence in these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has primarily situated communication challenges within children and family members, largely ignoring interpersonal factors. In recent years, however, a growing number of studies have shown that alignment – also often referred to as synchrony – can be socially meaningful in a variety of modalities, including movement, language, neurophysiology, and pupil dilation ( Pan et al, 2022 ; Nguyen et al, 2021 ); Wohltjen and Wheatley, 2021 ; Pickering and Garrod, 2021 ; Dikker et al, 2021b ). Here, we focus on neural synchrony, or inter-brain coupling, which has been associated with a range of communicative outcomes, including language comprehension, socio-emotional connectedness, learning, and even pain perception ( Goldstein et al, 2018 , Dumas et al, 2010 , Wass et al, 2020 , Davidesco et al, 2023 ; for reviews see e.g., Czeszumski et al, 2022 , Czeszumski et al, 2020 ; Koike et al, 2015 ; Tsoi et al, 2022 ; Babiloni and Astolfi, 2014 ; Toppi et al, 2016 ; Liu et al, 2018 ; Nguyen et al, 2020 ; Reindl et al, 2018 ; Marriott Haresign et al, 2022 ).…”
Section: Neural Alignment In Children Adults and Grandparentsmentioning
confidence: 99%